Los rincones de aprendizajes y su aporte al desarrollo de destrezas en los estudiantes del primer grado de educación general básica de la escuela Vicente Ramón Roca de la ciudad de Quevedo durante el presente año lectivo - Espinoza Delgado, Ángela Concepcion (2015)
This project explores the application of learning corners and the performance of the child to develop their skills achieving the capacity of exploration, research, reflection and enjoyment of learning; when you are speaking of work corners fully active methodology that develops through different free activities and aimed to achieve meaningful learning is analyzed. Today preschool students often use the game as the best form of distraction but when the teacher uses techniques of how to use the game to stimulate their learning, and that it will be of great help to them, this project also aims to contribute to the proper performance of the skills provided they have the corners to support their learning in the classroom. Ranging from pre Teachers as mediator of the teaching - learning of students is critical since learning will no longer be in vain, students utilize better corners no longer play by play, with the correct use of them develop their motor skills and teaching will be beneficial to their future life. This teaching method is based on an active methodology where the child is the builder of their own learning with teaching constitute a pedagogy of teaching and organization in the classroom, it is currently used on a regular basis and has large outstanding results in early childhood education and the child will not only benefit the most but also to teach it better with this great contribution and flattering method.